Strategi Membangun Kemampuan Representasi Matematis Siswa Di MI Al-Ma’arif 1 Kabupaten Sorong - Dewi Ayu IA; Nasrul Fauzi; Rusdin Rusdin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2020)
Strategy in the world of education is very important, in relation to building mathematical representation skills. A teacher not only focuses on student learning outcomes or student achievement but also, has planning in building student competencies, one of which is the ability mathematical representation. This study aims to analyze the initial ability mathematical representation of students and describe the strategies applied by the teacher in building mathematical representation skills at MI AL-Ma'arif Sorong Regency. This study uses a descriptive qualitative approach with the source of research data taken by purposive sampling, namely 3 students from the number of students in the class. Data collection techniques with the help of instruments, namely modules and mathematical representation videos, individual student math journals, problem packages mathematical representation, interviews, observations, and documentation. Analysis on student's journal of mathematics the mathematical representation used is only symbolic representation is verbal mathematical representation and visual representation almost absolutely do not students use it in solving or mathematical problem solving. Based on the data from the initial ability test results mathematical representation is still low based on ability indicators representation is 8.3, while the pretest score is 64.7. In describe the strategies that the teacher applies based on the results of the posttest undergoing changes and improvements based on indicators of ability representation is 16, while the posttest assessment is 97. The results showed that there was a strong relationship between students' mathematical strategies and representations. The conclusion obtained is strategies used by teachers in learning contribute to build students' mathematical representation skills, especially on fractions.